2008
DOI: 10.5194/hess-12-1229-2008
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating landscape characteristics in a distance metric for interpolating between observations of stream water chemistry

Abstract: Abstract. Spatial patterns of water chemistry along stream networks can be quantified using synoptic or "snapshot" sampling. The basic idea is to sample stream water at many points over a relatively short period of time. Even for intense sampling campaigns, the number of sample points is limited and interpolation methods, like kriging, are commonly used to produce continuous maps of water chemistry based on the point observations from the synoptic sampling. Interpolated concentrations are influenced heavily by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The combination of landscape characteristic and ω that resulted in the 24 lowest leave-one-out cross-validation K RMSE for each property was selected as the best 1 performing adjusted distance metric for interpolating that particular property. This is similar 2 to the methodology outlined by Lyon et al (2008). 3 4…”
supporting
confidence: 55%
See 3 more Smart Citations
“…The combination of landscape characteristic and ω that resulted in the 24 lowest leave-one-out cross-validation K RMSE for each property was selected as the best 1 performing adjusted distance metric for interpolating that particular property. This is similar 2 to the methodology outlined by Lyon et al (2008). 3 4…”
supporting
confidence: 55%
“…While there are conceptual similarities between this current study and the previous 12 work by Lyon et al (2008), it should be noted that the current study considers the local 13 landscape position influence on how samples collected in the landscape relate to each other. 14 This differs from Lyon et al (2008) where the focus is on adjusting path-restricted, in-stream 15 distances between stream water sampling positions based on the average composition of the 16 drainage area to a given sampling point. The current study interpolates point observations of 17 different properties in both the mineral and organic soil layers at the Ovanmyra field site in 18 central Sweden (Figure 1) using both a traditional distance metric and the adjusted distance 19 metric (Eq.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Speyrer and Ragas examined the impact of flood risk and mandatory flood insurance on property values (24). Several studies performed the popular SPARROW model using a hybrid approach combining conventional regression methods with spatial data based on landscape characteristics and stream properties to predict continuous water quality from point observations (25)(26)(27). Firat compared different models for daily river flow forecasting and concluded that adaptive neuro-fuzzy inference system (ANFIS) has higher accuracy and reliability than other models (28).…”
Section: Introductionmentioning
confidence: 99%